THE EFFECT OF TRAINING ON MUSCLE MASS DEVELOPMENT IN KONI DKI JAKARTA WUSHU ATHLETES - Junaidi Junaidi (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2023)
ABSTRACT Muscle mass is a part of body composition that is important for athletes’ health and performance, especially Wushu athletes. An optimal training program can increase athlete’s muscle mass, so it is necessary to evaluate muscle mass changing before and after the exercise program. The purpose of this program is to determine the effect of training on muscle mass development in PELATDA KONI DKI Jakarta Wushu athletes. Anthropometric and body composition examinations (muscle mass, skeletal muscle, and segmental muscle mass) were carried out before and after the exercise program. Examinations were carried out in June and September 2023. 20 of the 22 Wushu athletes took part in anthropometric and body composition examinations. Data was analyzed using the Paired Sample T test. Results showed that there was no significant difference between muscle mass, skeletal muscle and segmental muscle mass before and after the exercise program with >0.05 p value. Our findings show that the training program is less effective in increasing Wushu athletes’ muscle mass. Further research needs to be carried out to examine training programs and other supporting factors such as nutrition and recovery in increasing athletes’ muscle mass.